Formation of robust CEI film on high voltage LiNi0.6Co0.2Mn0.2O2 cathode enabled by functional [PIVM][TFSA] ionic liquid additive. (20th August 2022) - Cai, Yingjun; Xu, Tinghua; Meng, Xianglei; von Solms, Nicolas; Zhang, Haitao; Thomsen, Kaj
Highlights: A novel multifunctional ionic liquid was designed and synthesized using a two-step method. Physicochemical properties of the new ionic liquid with DMC and EMC were investigated. The cycle performance and rate properties were enhanced by adding an ionic liquid additive. The mechanisms were determined by CV, SEM and XPS analysis techniques. Abstract: The ionic liquid 1-(3-amino-3-oxopropyl)-3-vinylimidazolium bis(trifluoromethylsulfonyl)amide ([PIVM][TFSA]) was synthesized and applied in the electrolyte of Li/LiNi0.6 Co0.2 Mn0.2 O2 lithium ion batteries. The thermostability of this pure ionic liquid was investigated to provide a wide liquid range from -50 ℃ to 200 ℃. The physicochemical properties of binary mixtures of this ionic liquid with DMC and EMC were measured at different temperatures and with different ionic liquid mole fractions. [PIVM][TFSA] widens the electrochemical window of the electrolyte. The ionic liquid inhibits the increasing of water and HF content in the electrolyte. A comparison of charge and discharge performances in different electrolytes with various content of ionic liquid is reported. The electrolyte with the concentration of 1.0 wt % [PIVM][TFSA] has the best electrochemical properties. It enhances the initial capacity, the capacity retention and the high current rate performance of the cells. The surface film on the electrodes was confirmed by SEM and XPS that the ionic liquid [PIVM][TFSA] participated in membrane formation and played an active role. Graphical abstract: Image, graphical abstract